Kolaborasi Pustakawan Dalam Pengembangan Kompetensi dan Pelayanan Perpustakaan Digital Pada Masa Pandemi Covid-19 - Sheila Savitri (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2022)
By utilizing advances in information technology, The Indonesian Center for Agricultural Socio Economic and Policy (ICASEPS) Library expands its services through collaboration, not only with fellow librarian officials, but also other functional officials. As an effort to handle the impact of the Covid-19 Pandemic, the ICASEPS Library actively participates by providing accurate and useful information for the community. This study aims to provide an overview of the collaboration of librarians with other functional position holders in increasing their competence, as well as in improving digital library services during the Covid-19 Pandemic. The method used in this research is descriptive with simple statistical analysis. The data was obtained from the digital library service application via Google Form, Google Drive, and the official website of ICASEPS on the Covid-19 menu at http://pse.litbang.pertanian.go.id/ind/index.php/covid-19, starting from the implementation of the WFH policy, since March 2020 to July 2021. During the Covid-19 Pandemic, the ICASEPS Library carried out complex information retrieval services online, made ebook deposits together with researchers at ICASEPS, and collaborated with researchers, policy analysts, public relations, and computer engineers that proactively disseminate information related to Covid-19 through the Covid-19 feature on the ICASEPS website. ICASEPS librarian also collaborate with researchers and policy analysts in producing a scientific paper in a book publication entitled "The Impact of the Covid-19 Pandemic: Adaptation Perspectives and Agricultural Socio-Economic Resilience". The ICASEPS library also carries out promotions through social media channels. Various collaborations carried out by the ICASEPS Library, in addition to providing benefits for library development, are also for the development of librarian competencies.